Big Five personality traits in the workplace: Investigating personality differences between employees, supervisors, managers, and entrepreneurs - Kang, Weixi; Guzman, Kreisha Lou; Malvaso, Antonio (Frontiers in Psychology, 2023)
Personality relates to employment status. Previous studies have mainly compared the difference between entrepreneurs and managers. It remains unknown how personalities differ in entrepreneurs, managers, supervisors, and employees. In this research, we answer the questions by analyzing data from Understanding Society: the UK Household Longitudinal Study (UKHLS) that consisted of 2415 entrepreneurs, 3822 managers, 2446 supervisors, and 10897 employees. By using a multivariate analysis of variance (MANOVA) and ANOVA, we found that employment status has a significant multivariate effect on personality traits (F(5, 17159)=172.51, p<0.001) after taking account into demographics. Moreover, there were also significant univariate effects for Neuroticism (F(3,19502)=16.61, P<0.001), Openness (F(3,19502)=3.53, P<0.05), Agreeableness (F(3,19502)=66.57, P<0.001), Conscientiousness (F(3,19502)=16.39, P<0.001), and Extraversion (F(3,19502)=31.61, P<0.001) after controlling for demographics. Multiple comparisons revealed that entrepreneurs are characterized by low Neuroticism, high Openness, high Conscientiousness, and high Extraversion while managers had low Neuroticism, low Agreeableness, high Openness, and high Conscientiousness, and high Extraversion. Finally, supervisors are associated with high Conscientiousness. Implications and limitations are discussed.